MicroRNA expression profiles from HEK293 cells expressing H5N1 avian influenza virus non-structural protein 1. Issue 2 (February 2019) - Jiao, Hanwei; Zheng, Zonglin; Shuai, Xuehong; Wu, Li; Chen, Jixuan; Luo, Yichen; Zhao, Yu; Wang, Hongjun; Huang, Qingzhou
H5N1 avian influenza poses a serious threat to the poultry industry and human health. Non-structural protein 1 (NS1) plays an important role in the replication and pathogenesis of avian influenza virus (AIV). However, the function of the NS1 gene is still unclear. In this study, illumina genome analyzer iix screening was used to identify the differentially expressed microRNAs (miRNAs) in HEK293 cells expressing H5N1 AIV NS1. There were 13 differentially expressed miRNAs (hsa-miR-17-5p, hsa-miR-221-3p, hsa-miR-22-3p, hsa-miR-31-5p, hsa-miR-20a-5p, hsa-miR-222-3p, hsa-miR-24-3p, hsa-miR-3613-3p, hsa-miR-3178, hsa-miR-4505, hsa-miR-345-3p, hsa-miR-3648, and hsa-miR-455-3p) ( P  < 0.01). The qRT-PCR validation results demonstrated that hsa-miR-221-3p, hsa-miR-22-3p, hsa-miR-20a-5p, and hsa-miR-3613-3p were upregulated, while hsa-miR-3178 and hsa-miR-4505 were down-regulated. The softwares targetscan and miranda were further used to predict their target genes, and the gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis results showed that 20 GO terms and 20 KEGG pathways were significantly enriched. Our findings are the first to report expression profiling of miRNA and their functions in H5N1 AIV NS1-expressing HEK293 cells, and pave the way to further elucidating the accurate interaction mechanism between NS1 and virus replication, thus providing brand new insight into the prophylaxis and treatment of H5N1 AIV.